Novel Technology Smartal Exploring The Student Problem Analyzer For Mathematics Module - Umar, Siti Noor Arfah (2009)
A Pilot study was conducted by the team to find out for certain that teachers are actually disagreeing with SMM and would like improvements to be done on it. Other researches were conducted to find what elements are needed to design and develop the marketing plan for SMaRtal and also the functionality for the add-on modules. The qualitative research carried out by the researcher revealed that the subject of Mathematics can actually be implemented into the Student Problem Analyzer module. From this research, the design for the mathematics module of the Student Problem Analyzer is now complete and can thus be proceed to the development stage.